EXISTING FEEDING AND BREEDING MANAGEMENT PRACTICES FOR DAIRY ANIMALS IN SURAT DISTRICT OF GUJARAT (Indian Journal of Animal Production and Management, 2016)
The study was conducted purposively in Surat district to ascertain the feeding and breeding management  practices followed by rural dairy animal owners. A field survey was conducted during March, 2013 to  January, 2014 and data were collected from randomly selected 300 dairy animal owners through personal  interview with the help of pre-tested structured schedule from five talukas selected at random. The present  study revealed that all farmers adopted individual feeding system to their dairy animals and 81.67% of  respondents followed stall feeding system while, only 18.33% of respondents followed stall feeding as  well as grazing system. Majority (67%) of respondents cultivated green fodder crops and 64.33 and 99%  respondents fed green non-leguminous and bunds grass to their milking animals, respectively. Paddy  straw was major ingredient (75%) used as dry fodder. Sixty eight percent of respondents fed homemade  + compound cattle feed as concentrate to their milking animals, based on milk production (62.67%),  mainly after milking (57.67%). They fed concentrate to their animals after soaking in water while, 35% of  respondents fed concentrates as such. Most of respondents (95%) practiced to feed green/dry fodders  as such to their dairy animals. 52.33% of respondents did not fed concentrates to their young calves  while, 72% of respondents fed concentrates to their heifers. They practiced to feed concentrates to their  advanced pregnant heifers and 72.67% followed special feeding after calving. 58.33% of respondents  provided mineral supplements to their dairy animals. All the respondents detected heat in their animals  by observing the symptom of bellowing and mucus discharge (84.67%) and bred their animals by artificial  insemination (89.67%) between 12-18 hours after heat detection (95.67%). About 40% respondents bred  their animals after 2 to 3 months of calving and 89.33% respondents followed the pregnancy diagnosis  but 59.67% did it either from Livestock Inspectors or Artificial Insemination workers after three months of  breeding. Majority (54%) of respondents followed treatment of anoestrus/repeaters in their dairy animals  and only 7.67% of respondents kept the breeding records of their dairy animals.
Keywords: Breeding; Dairy animals; Feeding; Management; Practices; Surat district